BURNOUT SYNDROME IN ANESTHESIOLOGISTS AND INTENSIVE CARE PHYSICIANS - E. S. Netesin; V. I. Gorbachev; A. G. Nelyubin; O. E. Mitkinov (Acta Biomedica Scientifica, 2017)
The survey involved 130 anesthesiologists in the cities of Irkutsk and Ulan-Ude with the use of the MBI questionnaire - version for health professionals in adaptation of N.E. Vodopyanova allowed to study the prevalence and severity of various components of burnout syndrome (BOS). Sings of BOS were identified in doctors of young age; they most widely manifested as intense emotional exhaustion and depersonalization. Symptoms of emotional exhaustion begin to appear from the beginning of work and reach their maximum in the age group of 36-40 years, making 28 (24-32) score. Depersonalization as one of emotional burnout syndrome manifestations had a high level of 17 (15-19) points in 93 % of doctors aged from 35 to 45years. The most significant level of personal achievements reduction was noted in the age groups from 30 to 40 years (the average level - 32 (30-36) points). The resulting research data show that the daily work activity of anaesthesiologists causes significant professional harm and involves high responsibility, greater amount of work performed, working late shifts, which manifest themselves in the formation of personality deformation and development of the "stress associated with the difficulties of maintaining a normal lifestyle".